2016
DOI: 10.1364/oe.24.003365
|View full text |Cite
|
Sign up to set email alerts
|

Correlated photon pair generation in AlGaAs nanowaveguides via spontaneous four-wave mixing

Abstract: Abstract:We demonstrate a source of correlated photon pairs which will have applications in future integrated quantum photonic circuits. The source utilizes spontaneous four-wave mixing (SFWM) in a dispersion-engineered nanowaveguide made of AlGaAs, which has merits of negligible two-photon absorption and low spontaneous Raman scattering (SpRS). We observe a coincidence-to-accidental (CAR) ratio up to 177, mainly limited by propagation losses. Experimental results agree well with theoretical predictions of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 33 publications
(60 reference statements)
2
26
0
Order By: Relevance
“…The ZDW is located at ~1550 nm with the width of 700 nm (see Fig. 1c, and we have shown that this waveguide delivers efficient and broadband classical four-wave mixing (FWM) 24 . On the other hand, the TM mode is only slightly affected by the waveguide widths since the major electric field aligns vertically and experience less index contrast from the core-cladding interface.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The ZDW is located at ~1550 nm with the width of 700 nm (see Fig. 1c, and we have shown that this waveguide delivers efficient and broadband classical four-wave mixing (FWM) 24 . On the other hand, the TM mode is only slightly affected by the waveguide widths since the major electric field aligns vertically and experience less index contrast from the core-cladding interface.…”
Section: Resultsmentioning
confidence: 94%
“…We can estimate the bandwidth of SFWM using a classical FWM measurement 26 . Previously we reported co-polarized, continuous-wave FWM efficiencies measured from the 700-nm-wide waveguide 24 . The TE mode exhibited a bandwidth of at least 80 nm while the TM mode operated with a bandwidth of 60 nm.…”
Section: Resultsmentioning
confidence: 96%
“…Sources capable of these schemes need to emit photon pairs in a probabilistic manner with high brightness and low noise, preferably operating at telecom wavelengths that fit the high transmittance window of the optical fiber networks. In the past decades, photon-pair sources have been achieved through a variety of spontaneous nonlinear processes, including the spontaneous parametric down-conversion in optical crystals [6] and quasimatched waveguides [7], and the spontaneous fourwave mixing (SpFWM) in highly nonlinear fibers [8][9][10][11] and integrated waveguides [12][13][14][15][16][17][18][19][20]. Although the fiberbased source via SpFWM is more compatible with the optical fiber networks than the source via spontaneous * guokai07203@hotmail.com † yanglin61s@126.com parametric down-conversion, it suffers from the huge noise induced by the spontaneous Raman scattering of amorphous silica at room temperature [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a number of photon-pair generation experiments have been carried out in on-chip platforms, due to the advantages of designable dispersion and highly nonlinear response. The materials of these platforms include crystalline silicon [12][13][14][15][16], amorphous silicon [17], silica [18], silicon nitride [19], and (Al,Ga)As [20]. It is appealing to integrate significant building blocks for quantum communication on a single chip, the functionalities of which include photon-pair generation, photonpair modulation, cryptogram coding, and cryptogram decoding [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…As current data center communications systems use 850 nm vertical cavity lasers, monolithic integration would enable efficient wavelength division multiplexing devices [2]. AlGaAs has also been identified as the promising semiconductor system for quantum optics [3][4][5][6]. The integration of pump lasers, nonlinear optical elements, and signal processing waveguides opens the possibility of a true quantum optics technology.…”
mentioning
confidence: 99%